Pulsed Electrical Stimulation for Knee Osteoarthritis: Reappraisal of a 21-Year Clinical Development Program - Michael A. Mont; Chase W. Smitterberg; Javad Parvizi; Thomas Zizic (The Journal of Knee Surgery, 2026)
Abstract Knee osteoarthritis (OA) remains a leading cause of pain and disability, yet few nonoperative therapies have demonstrated durable clinical benefit or potential effects on structural disease progression. Pulsed electrical stimulation (PES) was investigated extensively over two decades, but this evidence has received little attention in the contemporary era of disease-modifying OA research. A structured evidence synthesis was performed of five principal prospective clinical investigations evaluating capacitively coupled PES for symptomatic knee OA. These included two randomized double-blind placebo-controlled trials, one multicenter phase IV investigation, one long-term observational study of arthroplasty deferral, and one histologic and radiographic study assessing structural cartilage changes. Collectively, the studies included 587 patients treated over more than 20 years. Clinical outcomes, functional improvement, medication utilization, safety, arthroplasty deferral, and structural findings were systematically reviewed and synthesized. Across investigations, PES consistently improved pain, physical function, physician and patient global assessments, and overall clinical status. Randomized controlled trials demonstrated significant improvements compared with placebo, while the multicenter phase IV study confirmed effectiveness in routine practice and identified a dose–response relationship, with superior outcomes following greater cumulative treatment exposure. Approximately 45% of patients reduced nonsteroidal anti-inflammatory drug use by at least 50%, and nearly 60% of compliant patients previously advised to undergo total knee arthroplasty deferred surgery for 4 years or longer. Tissue characterization in one patient, supported by radiographic observations in five additional patients, suggested hyaline-like cartilage formation and increased compartmental joint-space width. There were no serious device-related adverse events reported. More than two decades of prospective evidence suggest that PES improves pain, function, patient-reported outcomes, and clinical status while maintaining an excellent safety profile. These findings support a contemporary reappraisal of this technology as a nonoperative joint-preservation strategy for symptomatic knee OA.